Metal-based nanoparticle in cancer treatment: lessons learned and challenges - Hheidari, Ali; Mohammadi, Javad; Ghodousi, Maryam; Mahmoodi, Mohammadreza; Ebrahimi, Sina; Pishbin, Esmail; Rahdar, Abbas (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer, being one of the deadliest diseases, poses significant challenges despite the existence of traditional treatment approaches. This has led to a growing demand for innovative pharmaceutical agents that specifically target cancer cells for effective treatment. In recent years, the use of metal nanoparticles as a promising alternative to conventional therapies has gained prominence in cancer research. Metal nanoparticles exhibit unique properties that hold tremendous potential for various applications in cancer treatment. Studies have demonstrated that certain metals possess inherent or acquired anticancer capabilities through their surfaces. These properties make metal nanoparticles an attractive focus for therapeutic development. In this review, we will investigate the applicability of several distinct classes of metal nanoparticles for tumor targeting in cancer treatment. These classes may include gold, silver, iron oxide, and other metals with unique properties that can be exploited for therapeutic purposes. Additionally, we will provide a comprehensive summary of the risk factors associated with the therapeutic application of metal nanoparticles. Understanding and addressing these factors will be crucial for successful clinical translation and to mitigate any potential challenges or failures in the translation of metal nanoparticle-based therapies. By exploring the therapeutic potential of metal nanoparticles and identifying the associated risk factors, this review aims to contribute to the advancement of cancer treatment strategies. The anticipated outcome of this review is to provide valuable insights and pave the way for the advancement of effective and targeted therapies utilizing metal nanoparticles specifically for cancer patients.